Frailty in cardiology: definition, assessment and clinical implications for general cardiology. A consensus document of the Council for Cardiology Practice (CCP), Association for Acute Cardio Vascular Care (ACVC), Association of Cardiovascular Nursing and Allied Professions (ACNAP), European Association of Preventive Cardiology (EAPC), European Heart Rhythm Association (EHRA), Council on Valvular Heart Diseases (VHD), Council on Hypertension (CHT), Council of Cardio-Oncology (CCO), Working Group (WG) Aorta and Peripheral Vascular Diseases, WG e-Cardiology, WG Thrombosis, of the European Society of Cardiology, European Primary Care Cardiology Society (EPCCS). (16th July 2021) - Richter, Dimitri; Guasti, Luigina; Walker, David; Lambrinou, Ekaterini; Lionis, Christos; Abreu, Ana; Savelieva, Irina; Fumagalli, Stefano; Bo, Mario; Rocca, Bianca; Jensen, Magnus T; Pierard, Luc; et al.
Abstract: Frailty is a health condition leading to many adverse clinical outcomes. The relationship between frailty and advanced age, multimorbidity and disability has a significant impact on healthcare systems. Frailty increases cardiovascular (CV) morbidity and mortality both in patients with or without known CV disease. Though the recognition of this additional risk factor has become increasingly clinically relevant in CV diseases, uncertainty remains about operative definitions, screening, assessment, and management of frailty. Since the burdens of frailty components and domains may vary in the various CV diseases and clinical settings, the relevance of specific frailty-related aspects may be different. Understanding these issues may allow general cardiologists a clearer focus on frailty in CV diseases and thereby make more tailored clinical decisions and therapeutic choices in outpatients. Guidance on identification and management of frailty are sparse and an international consensus document on frailty in general cardiology is lacking. Moreover, new options linked with eHealth are going to better define and manage frailty. This consensus document on definition, assessment, clinical implications, and management of frailty provides an input to integrate strategies pre- and post-acute CV events with a comprehensive view including out of hospital, office-based diagnostic and therapeutic choices, and based on a multidisciplinary team approach (general cardiologists, nurses, and general practitioners).